"CLINICAL OUTCOME OF HIV INFECTED PATIENTS ACCORDING TO IMMUNOLOGIC RESPONSE AFTER HIGHLY ACTIVE ANTIRETROVIRAL THERAPY " - M. Rasoolinejad; M. Hajabdolbaghi; M. Mohraz; N. Zarinfar; S. A. Mohajerani (Acta Medica Iranica, 2005)
Current mainstay of treatment for human immunodeficiency virus (HIV)-infected patients is highly active antiretroviral therapy (HAART) but little is known about the long-term clinical outcome for HIV-infected patients who have received HAART. Determining factors associated with longterm survival in the course of treatment may allow modification to be made for patients who are at a greater risk of treatment failure. In this study patients who were under HAART from March 2002 to September 2003 were evaluated. They were visited from 2 to 5 times and clinical and lab findings and CD4 count on every visit were recorded. Rates of progression from the initiation of HAART to treatment failure, defined as constant decline of CD4 numbers, occurrence of AIDS criteria and death, were determined. Forty three patients, 31 male and 12 female, with an average age of 39.6 were selected. The most common finding on initiation of treatment in these patients was wasting syndrome (16.3%). Overall, treatment failure occurred in 37.2%. Mean time to treatment failure was 13.3 months. There was correlation between baseline CD4 and survival of patients with history of monotherapy (P